The Influence of Online and Offline Health Counseling on Covid-19 Prevention for Pregnant Women - Ningsih, Fitria; Irawati, Nuzulia; Evareni, Lisma (poltekkes kemenkes mataram, 2024)
There were 399 pregnant women who suffered from COVID-19 in Padang in 2021 and the highest number of cases happened in Andalas Health Center. The Objective of this research was to determine the influence of health counseling using online and offline media about covid-19 prevention on the knowledge, attitudes, and actions of pregnant women in the work area of Andalas Health Center of Padang in 2022. This research was a quasy experiment with a two-group pre-posttest group design. The research was carried out in the work area of Andalas Health Center Padang on March 2021 - August 2022. The population was all pregnant women in Andalas Health Center Padang and the samples were 60 pregnant women in two groups; 30 cases and 30 controls. The bivariate analysis used Wilcoxon and Paired Sample T-Test, p <0,05. There was an influence of counseling on knowledge, attitudes, and actions in online media groups (p=0.027, p=0.039, and p=0.032). There was an influence of counseling on knowledge and action (p=0,010; p=0,024) but there was no influence on attitudes in the offline media group (p=0,063). There were differences in the influence of health counseling on preventing COVID-19 used online and offline media with different means were 1.7, 12.7, and 1,7. In conclusion, there was differences in the influence of health counseling using online and offline media on COVID-19 prevention on the knowledge, attitudes, and actions of pregnant women and health counseling using offline media was better than the online. Keywords: Knowledge, Attitudes, Actions, Prevention of COVID-19, Pregnant Women.